Répétition et différenciation dans les reprises structurelles intégrant des relatives - Stoenica, Ioana-Maria (My University, 2014)
Drawing on a corpus of 5 hours of audio-recorded French talk-in-interaction, this paper addresses the issue of the role of structural repetitions integrating relative clauses in the organization of the interaction. Previous works on repetition have mainly focused on the study of specific sequential placements where different forms of repetition occurred. This paper provides a different insight into the study of repetition, by concentrating on a specific grammatical structure, the relative clause, throughout its sequentially and temporally deployed repetitions. Using the framework of interactional linguistics, this study shows that the structural repetitions integrating relative clauses bring about assimilation of one’s speech but also and foremost a difference that unfolds temporally, once with the deployment of turns at talk and that is constructed sequentially, being influenced by the ecology of its interactional environment. This paper presents thus an empirically grounded argument about the interlocutors’ use of relative clauses as resources for all practical purposes.